Selection and Validation of Reference Genes for RT-qPCR Analysis of the Ladybird Beetle Henosepilachna vigintioctomaculata - Lü, Jing; Chen, Shimin; Guo, Mujuan; Ye, Cuiyi; Qiu, Baoli; Wu, Jianhui; Yang, Chunxiao; Pan, Huipeng (Frontiers in Physiology, 2018)
Reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR), is an important technique for quantifying gene expression profiling of targeted gene across various biological processes. Selection and validation of appropriate reference genes for RT-qPCR normalization is a pivotal precondition for reliable expression measurement. Henosepilachna vigintioctopunctata is one of the most important pests attacking Solanaceae crops in Asian countries. Recently, the transcriptomes of H. vigintioctopunctata were sequenced, this promote the gene functional studies of this insect pest. Unfortunately, reference genes have not been previously selected and validated in H. vigintioctopunctata. In this study, a total of seven commonly used reference genes including Actin, GAPDH, RPL13, RPL6, RPL32, RPS18, and ATPB were selected and assessed of its suitability under four experimental conditions including developmental stage, tissue, temperature, and host plant using RefFinder which integrates four different analytical tools geNorm, Normfinder, BestKeeper, and the ΔCt method. The results showed that RPL13 and RPS18 were enough and the best reference genes for each experimental condition, respectively. The relative expression levels of two target genes lov and TBX1 varied greatly according to normalization with the two most- and -least suited reference genes. Our results will be useful for improving the accuracy of RT-qPCR analysis for future functional studies of target gene expression in H. vigintioctopunctata.